Birds in Eighteenth-Century Literature
XIV, 284 p. 9 illus.
Keywords: This book examines literary representations of birds from across the world in an age of expanding European colonialism. It offers important new perspectives into the ways birds populate and generate cultural meaning in a variety of literary and non-literary genres from 1700–1840 as well as throughout a broad range of ecosystems and bioregions. It considers a wide range of authors, including some of the most celebrated figures in eighteenth-century literature such as John Gay, Henry Fielding, Laurence Sterne, Anna Letitia Barbauld, William Cowper, Mary Wollstonecraft, Thomas Bewick, Charlotte Smith, William Wordsworth, and Gilbert White.